Main factors influencing the electro-methanation of CO_2 in microbial electrolytic cells and the role of electron intermediates - ZHEN Guangyin*; WANG Na; WANG Jiayi; LU Xueqin; QIU Boran (能源环境保护)
Greenhouse gas emissions from fossil fuel combustion have led to global ecological degradation and energy crisis. Therefore, it is urgent to explore new technologies for the conversion, reuse and clean energy production of carbon dioxide (CO_2). Compared with the conventional technology of converting CO_2 into high-value products, the conversion of CO_2 into methane (CH_4), a low-carbon energy source, using microbial electrolysis cell (MEC) has the advantages of mild reaction conditions, recyclable catalysts and green products, and has received a lot of attention from researchers. This paper reviews the current research status of CO_2 capture and high-value resource utilization, and discusses the main influencing factors of MEC-CO_2 electromethanation (such as inoculum source, reactor configuration, applied voltage, electrode material properties, etc.), briefly outlines the important role of electron shuttles, especially riboflavin, in MEC-CO_2 electromethanation and the biofilm formation process of electric methanogenic bacteria, points out the current technical bottleneck and future research direction of MEC-CO_2 electromethanation, and finally provides theoretical support for the development of MEC-CO_2 electromethanation and the realization of "dual carbon" goal.